Association between environmental allergen sensitization with severity of atopic dermatitis in children and young adult at Dr. Sardjito General Hospital, Yogyakarta - Herwinda Brahmanti; Niken Trisnowati; Retno Danarti; Hardyanto Soebono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
The important role of aeroallergens and food allergens as the most common environmental allergens in exacerbationof atopic dermatitis (AD) iswell known. Sensitization is an essential processwhich correlateswith clinicalmanifestationof AD. The study of AD in Indonesia, especially in Yogyakarta, has not been reported, yet. The aim of study is toevaluate the association between sensitization of environmental allergens with clinical severity of AD in children andyoung adult at Dr. Sardjito General Hospital, Yogyakarta. An analytic observational cross sectional study wasperformed on 33 children and young adult with AD. The severity of disease was determined by SCORing AtopicDermatitis (SCORAD). Assessment of sensitization was performed using specific IgE serum, atopy patch test, andprick test. Data were analyzed using chi-square or Fisher exact test and prevalence ratio (PR) with significancevalue of p<0.05 and 95%confidence interval (CI). The results showed that specific IgE positivity was associatedwith severity of AD. Percentage of specific IgE positivity to house dust mite was significantly higher in subject withmoderate/severe AD compared to those of mild AD (p=0.049; PR 1.13; 95% CI 1.01-1.59). The result was alsosimilar for cat dander (p=0.041; PR 1.1; 95%CI 1.09-4.98), cow’s milk (p=0.038; PR 1.21; 95% CI 1.02-2.2),and egg white (p=0.027; PR 1.23; 95% CI 1.15-2.97). Whereas specific IgE positivity to fish allergen was notstatistically different in subject with moderate/severe AD compared to those with mild AD (p=0.061; PR 0.8; 95%CI 0.76-2.8). According to atopy patch test and prick test result, no association was found between allergensensitization and severity of AD. If allmethodswere combined to increase the sensitivity of sensitizationmeasurement,then the association was found for all allergens. It could be concluded that environmental allergens sensitization isassociated with severity of AD in children and young adult at Dr. Sardjito General Hospital, Yogyakarta.Key words: atopic dermatitis-disease severity-sensitization-aeroallergen-food allergen